A picture is worth a thousand words: a photo-thematic analysis of city hospitality in municipal popular reporting. (28th December 2021) - Del Gesso, Carla
Abstract : Purpose: This paper aims to study the disclosure of information about city hospitality within municipal popular reporting documents, by conducting a photo-thematic analysis of the photographic imagery contained therein. These documents have great potential for integrating supplementary information in a simplified, short and attractive form. Supplementary disclosure by means of pictures, such as that concerning city hospitality, has not previously been researched. Design/methodology/approach: This qualitative research uses visual data, specifically photographs, as a data source. To capture city hospitality disclosure, a photo-thematic analysis was conducted on a total of 495 photographs contained in a sample of 30 US municipal Popular Annual Financial Reports singled out for best practice. Photographs were inductively thematized using the qualitative data analysis software "QDA Miner". Findings: The photo-thematic analysis yielded an array of themes and sub-themes important to an overall understanding of municipal government disclosure about city hospitality. Going far beyond hosting the hospitality industry segment, city hospitality proved to be a complex area involving city livability and sustainability; it encompasses environmental and landscape resources, facilities, services, activities, events, culture, history, sociability, innovation and much more. Photographs were able to suitably provide supplementary nonfinancial disclosure in popular reports, conveying a welcoming image to the city's guests – including both its citizens and visitors – in a timely and appealing way. Originality/value: This study is the first to examine information disclosure via photographs in popular reporting, focusing on municipal government disclosures about city hospitality. It, therefore, offers new knowledge in both the areas of city hospitality and popular reporting, using an innovative qualitative research approach which gives insight into the power of pictures to generate and convey information beyond textual data. Abstract : 图胜千言：市政流行报告中基于城市好客度的图片主题分析 研究目的: 本研究通过市政流行报告中基于城市好客度的相关图片进行主题分析。这些文件为整合补充信息从而提炼成为简化和有吸引力的信息形式提供强大潜力。通过图片来做为补充信息, 例如城市好客度, 并未在前人研究出现。 研究设计/方法/途径: 本论文运用了视觉数据, 尤其是图片作为数据源。为了诠释城市好客度, 本研究对由30个美国流行年度财务报告 (PAFRs) 作为样本中的495张图片来进行图片主题分析。本研究将这些图片运用归纳主题分析法通过定性数据软件QDA进行分析。 研究结果: 图片主题分析产生了一系列衡量城市好客度有重要影响力的主题和分主题。非局限于开发酒店行业, 城市好客度被证实其概念更加复杂并涉及城市宜居性和可持续程度; 其主要包含环境资源, 城市设施, 服务, 活动, 节事, 文化, 历史, 社交性, 创新性和更多。图片可以更合适的在流行年度报告中提供补充性, 非财务性的信息, 从而向城市宾客 – 本市居民以及访客 –用及时和更具吸引力的方式传递好客的城市形象。 研究原创性/价值: 本研究首创性的运用城市政府报告中含城市好客度为焦点, 通过图片来提取信息。运用了创新性定性研究方法来从图片提取非文字可传递的信息, 从而为城市好客度和流行报告方面的研究提供新知识。